Model Manajemen Madrasah Berbasis Data dan Nilai Islam dalam Pengambilan Keputusan - M. Asep Fathur Rozi; Moch. Rizal Fuadiy (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2026)
Data-driven decision-making has become increasingly important in educational management, yet its application in madrasah contexts requires attention not only to empirical evidence but also to the Islamic values that shape institutional practices. Previous discussions have largely addressed data-based management and Islamic educational values separately, leaving limited understanding of how both dimensions are integrated within managerial decision-making. This study aims to analyze the utilization of institutional data, examine the role of Islamic values in the decision-making process, and formulate a management model that integrates data and Islamic values at MTs Taufiqiyyatul Asna Pare. This study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation and analyzed through data condensation, data display, and conclusion drawing. The findings reveal that the madrasah uses academic, attendance, discipline, achievement, and service data as considerations in managerial decision-making. However, data utilization is selective and contextual, with attendance and discipline data being used more frequently because of their direct relevance to daily operational problems. The findings further demonstrate that data do not automatically determine decisions. Instead, empirical information is interpreted and deliberated through musyawarah, oriented toward consensus (mufakat), and guided by the principle of justice. The study proposes a madrasah management model in which data serve as an empirical basis for identifying problems, while Islamic values guide the deliberation, determination, implementation, and evaluation of decisions. This model contributes to a more evidence-informed, participatory, and value-oriented approach to educational management in madrasah contexts.